Analisis Implementasi Kebijakan Angkutan Umum oleh Pemerintah Kabupaten Sijunjung dalam Perspektif Fiqih Siyasah Tanfidziyah - Daswita; Raymond Dantes (AHKAM, 2026)
Public transportation is a basic societal need whose provision is the responsibility of the government, as stipulated in Government Regulation Number 74 of 2014 concerning Road Transportation. However, in recent years, Sijunjung Regency has faced a shortage of public transportation that has even led toward the disappearance of such services. This study aims to analyze the implementation of public transportation policy based on Government Regulation Number 74 of 2014 and examine it from the perspective of fiqh siyasah tanfidhiyyah. The study employed a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation. The findings indicate that the implementation of public transportation policy in Sijunjung Regency has not been effective because several requirements, such as the obligation to obtain legal entity status, high licensing costs, and stringent vehicle standards, are not aligned with the region’s economic and geographical conditions. From the perspective of fiqh siyasah tanfidhiyyah, the policy has not fully realized the public interest because its implementation has instead created difficulties for the community and transportation operators and has not reflected the principles of justice and the prohibition against burdening people beyond their capacity. This study concludes that the implementation of public transportation policy requires adjustment to the region’s social, economic, and geographical conditions to become more effective, equitable, and oriented toward public welfare. These findings have implications for local governments in formulating more adaptive implementation policies to ensure the sustainability of public transportation services in Sijunjung Regency.